LY2495655, an antimyostatin antibody in pancreatic cancer: a randomized phase 2 trial - Golan, Talia; Geva, Ravit; Richards, Donald; Madhusudan, Srinivasan; Lin, Boris Kin; Wang, Haofei Tiffany; Walgren, Richard A.; Stemmer, Salomon M. (Wiley, 2018)
Background: Cachexia is a formidable clinical challenge in pancreatic cancer. We assessed LY2495655 (antimyostatin antibody) plus standard-of-care chemotherapy in pancreatic cancer using cachexia status as a stratifier.